(untitled) (Research, Society and Development, 2021)
Childhood is a phase of life that, for the most part, is symbolized by the act of playing. It is through this stage that the child has new skills, experiences, and discoveries. In addition, one can also notice the development of processes such as creativity, self-confidence, social-affective relationships, and cognition. However, some situations sometimes hinder the realization of processes that are essential for childhood, hospitalization being one of them. The study aims to know the playful strategies in the scenario of pediatric hospitalization, highlighting its benefits and importance in hospital humanization. This is an integrative review, carried out from articles collected from the Scielo, PubMed, Lilacs, Medline and BDENF databases. The descriptors applied were "Child Health" AND "Play Therapy". The findings showed that play strategies are extremely important in the humanization of care for hospitalized children, as they reduce suffering and make hospitalization less painful and traumatic. It was concluded that playful strategies when implemented in the pediatric hospital setting promote a less traumatic recovery, in addition to allowing for greater tranquility in the hospital environment. Moreover, the use of playful strategies was pointed out by the studies as a communication resource that benefits not only the physical, emotional, and immunological stimuli, but also the relationship between the child and the health professional, thus contributing to a greater trust in the therapy adopted and in the multiprofessional team.